PENGARUH PENERAPAN METODE BRAINSTORMING TERHADAP MOTIVASI DAN HASIL BELAJAR PADA PEMBELAJARAN TEMATIK INTEGRATIF DI SDN 1 LANGKO - Gazali, Munawir; Hasanah, Husnul (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This research aims to describe the effect of applying the Brainstorming method on motivation and learning outcomes in integrative thematic learning for class V students. This research is a quasi-experimental research, with a pretest-posttest design with nonequivalent groups. The population in this study were class V students of SDN 1 Langko, first semester of the 2023/2024 academic year. Two classes were taken randomly, each consisting of an experimental group of 33 students and a control group of 33 students. Pretest and Posttest are used to measure student motivation and learning outcomes. The validity and reliability of the instrument were calculated using the SPSS 17.00 for Windows program. Data analysis uses independent t test statistics to determine the effect of learning methods which include the brainstorming method in the experimental class and conventional methods in the control class. The results of this research show that there is a positive and significant influence of the brainstorming method on the motivation and learning outcomes of SDN 1 Langko students on the sub-theme of togetherness in diversity. It is proven from the results of the t-test with a significance of 0.000 in the experimental group, meaning that the brainstorming method is able to increase motivation and learning outcomes for the sub-theme of togetherness in the diversity of SDN1 Langko participants.